PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN PADA MATERI MATEMATIKA EKONOMI DENGAN PENDEKATAN ETNOPEDAGOGI TERHADAP MOTIVASI DAN HASIL BELAJAR MAHASISWA - Achmad Buchori; Siti Kholifah (LPPM Universitas Bina Bangsa, 2022)
The purpose of this study was to find out that instructional video media with an Ethnopedagogical approach are valid and can increase student motivation and learning outcomes. Until now, students are still not optimal in their motivation and learning outcomes in economic mathematics. local wisdom values. This study uses research and development (Research and Development) methods with the ADDIE learning model which uses 5 stages using instruments, namely questionnaires and post tests in the form of answers to evaluation questions to find out from the media. The development procedures in this study include: (1) analysis of student needs, curriculum and materials, (2) Designing media designs, (3) Developing media designs, (4) Testing the feasibility of media designs, and (5) evaluating media designs, the research was conducted in the UPGRIS Semarang Mathematics Education Study Program and D4 Computerized Accounting Study Program at STEKOM Semarang University. Based on the validation results from the validator, the acquisition of a very good score from member learning media experts obtained 97.3%, learning material experts obtained 90%. The subjects in the study that collected data were 27 students from the experimental class and 27 students from the control class. While in the trial phase there were 28 students who had received economic mathematics material. Based on the results of the study it was concluded that instructional video media with an ethnopedagogical approach to motivation and learning outcomes of UPGRIS Mathematics Education students and D4 study program Computerized accounting at STEKOM Semarang university are valid, can increase learning motivation in the very good category, and can improve student learning outcomes